Penerapan Enterprise Risk Management dalam Meningkatkan Kinerja Keuangan di Perusahaan “XYZ” - Pranatha, Mohamad A’ar; Moeljadi, Moeljadi; Hernawati, Erna (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
The research will be discussed about the impact of the implementation of Enterprise Risk Management in improving financial performance in Company